Phenomenon of Love Scam Cases in Legal Practice: Exploring Case Construction and Victim Responses - Bunga, Dewi; Arsawati, Ni Nyoman Juwita; Budiana, I Nyoman (International Journal of Law Reconstruction, 2025)
A new mode of online fraud is loving scamming, namely using social media or dating applications to commit fraud by building interpersonal relationships between the perpetrator and the victim. Love scammers will target victims and communicate continuously so that they have a love relationship. After an emotional bond, the perpetrator will ask for money with the mode of needing money for urgent needs. Three problems will be discussed: the analysis of love scams in the vortex of cybercrime, the construction of love scam cases in the Law of the Republic of Indonesia Number 1 of 2024, and the victims' response and when they can report it. Love scam is a crime committed in cyberspace; therefore, electronic evidence is essential for uncovering cases when they reach the police. Not all gifts based on a love relationship can be reported. Several criminal provisions in Law Number 1 of 2024 can be used to ensnare perpetrators. In legal practice, not all victims want to report love scams that have happened to them. Some victims do not realize they are victims; some victims deliberately do not report because they are embarrassed and to avoid social judgment; some do not have evidence.